2021
DOI: 10.1126/scitranslmed.aaz5380
|View full text |Cite
|
Sign up to set email alerts
|

Elastin-like recombinamers-based hydrogel modulates post-ischemic remodeling in a non-transmural myocardial infarction in sheep

Abstract: Ischemic heart disease is a leading cause of mortality due to irreversible damage to cardiac muscle. Inspired by the post-ischemic microenvironment, we devised an extracellular matrix (ECM)–mimicking hydrogel using catalyst-free click chemistry covalent bonding between two elastin-like recombinamers (ELRs). The resulting customized hydrogel included functional domains for cell adhesion and protease cleavage sites, sensitive to cleavage by matrix metalloproteases overexpressed after myocardial infarction (MI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 81 publications
1
60
0
Order By: Relevance
“…This would suggest that injectable hydrogels have the ability to retain the highly complex and intricate architecture of the heart post-MI, resulting in increased EF [ 2 ]. This would be in line with the findings of studies [ 13 , 14 , 15 , 16 , 17 , 18 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 30 ], which reported both attenuated LV remodeling and an increase in EF.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This would suggest that injectable hydrogels have the ability to retain the highly complex and intricate architecture of the heart post-MI, resulting in increased EF [ 2 ]. This would be in line with the findings of studies [ 13 , 14 , 15 , 16 , 17 , 18 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 30 ], which reported both attenuated LV remodeling and an increase in EF.…”
Section: Resultssupporting
confidence: 92%
“…The hydrogel characterization and its mode of delivery are tabulated in Table 2 . Few studies reported the delivery of injectable hydrogel without a cellular component [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ], while the rest chose a different composition of cells and type of matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although still in their infancy, the move toward a synthetic ECM hydrogel will facilitate the clinical usability of such a therapeutic strategy. A recent study has demonstrated the potential of this by developing a degradable elastin-like polypeptide hydrogel, which mimics the ECM ( 61 ). Intramyocardial injection of this hydrogel in a sheep model for myocardial infarction lead to a reduction in fibrosis, increased angiogenesis, improved cardiac function and cardiomyocyte integrity in the border zone of the infarcts ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated the potential of this by developing a degradable elastin-like polypeptide hydrogel, which mimics the ECM ( 61 ). Intramyocardial injection of this hydrogel in a sheep model for myocardial infarction lead to a reduction in fibrosis, increased angiogenesis, improved cardiac function and cardiomyocyte integrity in the border zone of the infarcts ( 61 ). Taken together, these steps will not only help our understanding of cardiac regeneration as a whole, but will also lead to an improved outcome for patients suffering from HF.…”
Section: Discussionmentioning
confidence: 99%